2020
DOI: 10.21037/cdt.2019.09.12
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement in low risk patients: a review of PARTNER 3 and Evolut low risk trials

Abstract: Transcatheter aortic valve replacement (TAVR) has become a mainstay in treatment for patients with severe aortic stenosis who are considered high-risk surgical candidates. The use of TAVR in low-risk patients with severe aortic stenosis is being explored as an alternative to surgical aortic valve replacement (SAVR). Recent results from the Medtronic Evolut Low Risk trial and the Placement of Aortic Transcatheter Valves (PARTNER) 3 trial shed light on the use of TAVR in low-risk surgical candidates. The Evolut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 52 publications
(69 reference statements)
1
29
0
1
Order By: Relevance
“…It is proposed that the good performance of SAPIEN 3 in BAVs is likely due to the high radial strength offered by the metallic steel frame. Recently, clinical findings with the Evolut R and Pro devices on bicuspid patients have been documented [18]. It is worth noting that both the self-expanding and balloon-expandable devices are characterized by a longer sealing skirt to avoid the leakage as compared to the previous generation.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that the good performance of SAPIEN 3 in BAVs is likely due to the high radial strength offered by the metallic steel frame. Recently, clinical findings with the Evolut R and Pro devices on bicuspid patients have been documented [18]. It is worth noting that both the self-expanding and balloon-expandable devices are characterized by a longer sealing skirt to avoid the leakage as compared to the previous generation.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter aortic valve repair (TAVR) is a minimally invasive procedure for the treatment of severe AS. It is becoming an increasingly more utilized treatment option over traditional surgical aortic valve replacement (SAVR) in many patient populations [2]. The major driving factor to this trend is due to emerging data showing an overall decrease in mortality and procedure-related complications coupled with patients and physicians' desire for the less invasive procedures [3].…”
Section: Introductionmentioning
confidence: 99%
“…As further research continues, subsequent clinical trials showed TAVR noninferiority to SAVR for both high and intermediate surgical risk patients [5]. During the most recent clinical trials, Placement of Aortic Transcatheter Valves (PARTNER) 3 and Evolut R, TAVR was shown to be a noninferior and, in some cases, superior alternative to SAVR for low surgical risk patients due to decreased mortality and non-inferiority, respectively [2,6,7]. As the indications for TAVR continue to expand, several periprocedural and postprocedural complications have gained interest in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…We agree that in general very young patients should have an SAVR with a mechanical prosthesis. There are some promising factors of TAVR that are also worth considering such as the lower risk of atrial fibrillation and shorter hospitalizations, 19 and the 5-year NOTION trial data showing larger prosthetic valve area and lower mean gradients with TAVR compared with SAVR in low-risk patients. 20 In addition, mortality and stroke have improved over the past decade with TAVRs probably due to a combination of experience with the procedure and patient selection, higher volume of procedures, and improvement in the valve systems.…”
mentioning
confidence: 99%